2020
DOI: 10.1371/journal.pntd.0008843
|View full text |Cite
|
Sign up to set email alerts
|

Comparing machine learning with case-control models to identify confirmed dengue cases

Abstract: In recent decades, the global incidence of dengue has increased. Affected countries have responded with more effective surveillance strategies to detect outbreaks early, monitor the trends, and implement prevention and control measures. We have applied newly developed machine learning approaches to identify laboratory-confirmed dengue cases from 4,894 emergency department patients with dengue-like illness (DLI) who received laboratory tests. Among them, 60.11% (2942 cases) were confirmed to have dengue. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 61 publications
4
68
0
2
Order By: Relevance
“…Although these three are common arboviral diseases, no studies were found that carried out multi-classification considering these arboviral diseases or other arboviral types, such as West Nile virus, yellow fever virus, Saint Louis Encephalitis virus, Mayaro virus, Oropouche virus and others, showing that there are space for further investigations in this area. Most of works presented models for binary classification: Dengue or not [40][41][42][43][44][45]; DHF or not [46]; Chikungunya or not [47]; and Zika classified between "Discarded cases" and "Somewhat probable" for CZS [48]. It is interesting to note that the only work that deals with Zika is focused on CZS, not covering Zika in general.…”
Section: What Arboviruses Are the Focus Of Research On Machinementioning
confidence: 99%
See 4 more Smart Citations
“…Although these three are common arboviral diseases, no studies were found that carried out multi-classification considering these arboviral diseases or other arboviral types, such as West Nile virus, yellow fever virus, Saint Louis Encephalitis virus, Mayaro virus, Oropouche virus and others, showing that there are space for further investigations in this area. Most of works presented models for binary classification: Dengue or not [40][41][42][43][44][45]; DHF or not [46]; Chikungunya or not [47]; and Zika classified between "Discarded cases" and "Somewhat probable" for CZS [48]. It is interesting to note that the only work that deals with Zika is focused on CZS, not covering Zika in general.…”
Section: What Arboviruses Are the Focus Of Research On Machinementioning
confidence: 99%
“…As disadvantages, this type of model does not generalise well when using a large number of features, it is vulnerable to overfitting, and cannot solve non-linear problems, requiring a transformation of non-linear resources [74]. Two works employed Logistic Regression in the sample - [45] and [50].…”
Section: Logistic Regressionmentioning
confidence: 99%
See 3 more Smart Citations